SyMPLES : uma abordagem de desenvolvimento de linha de produto para sistemas embarcados baseada em SysML - Silva, Rogério Ferreira da (2012)
The evolution of hardware platforms has been allowed to move a larger amount of functionality to embedded systems software. This way, software has become increasingly complex. Several techniques have been proposed over the years for dealing with complexity, including: the application of object orientation concepts to high-level models and the software product line (PL) approach. The object-oriented methods allow the creation of a series of models in which the level of details can be increased during the development process. The PL approach applied in the field of embedded systems enables to build a family of products in which different members vary in terms of their behavior, quality attributes, platform, physical configuration, and others. This master thesis proposes the SyMPLES approach that combines high-level models and the PL approach for the development of embedded systems. SyMPLES uses the language SysML for representation as a basis for LP Models. We have defined two extensions for SysML through the profiling mechanism: the SyMPLES-ProfileVar to express the variability concepts; and SyMPLES-ProfileFB to assign the blocks SysML with major classes of functional blocks, approach widely used in the specification of embedded systems. In addition, two processes were defined to assist the engineer in specifying the PL: the SyMPLES-ProcessPL that defines a set of activities and guidelines to guide the engineer in the construction of the PL artifacts; and SyMPLES-ProcessVar that defines a set of activities and guidelines for identification and demarcation of variability, and systematizes the product configuration. As an example application of the approach, a PL was created for two subsystems of the unmanned aerial vehicle (UAV) Tiriba, developed in the context of the National Institute of Science and Technology for Critical Embedded Systems (INCT-SEC).